Market Reaction to the 2024 Election Results: Prabowo-Gibran's Presidential Announcement: (Study on LQ-45 Companies) - Na’im, Arif Ainun; Hasnawati, Sri (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study examines the capital market's reaction to the announcement of Prabowo-Gibran’s victory in the 2024 Indonesian presidential election by the General Elections Commission (KPU) using event study methodology. The research focuses on abnormal returns, trading volume activity (TVA), and security return variability (SRV) of companies listed in the LQ-45 index. Data was collected for an event window spanning five days before and after the announcement. The results show no significant changes in abnormal returns, indicating that the market had already priced in the expected outcome prior to the official announcement. Trading volume activity increased slightly but this change was also not statistically significant,suggesting that the announcement did not introduce substantial new information. Similarly, SRV decreased slightly but not significantly, pointing to a relatively stable market reaction. The findings align with the Efficient Market Hypothesis, suggesting that the market had already absorbed the election outcome based on early survey data. These results contrast with previous studies that identified significant market reactions to political events, highlighting the unique nature of investor behavior in this particular event.